Converging modalities for distance education in professional communication: Implications from flexible delivery - Ray Archee; Shirley Saunders (Flexible Learning Association of New Zealand, 2012)
Distance education (in the United States of America) and flexible learning (in the United Kingdom) are popular catch-phrases that utilise the Web and other electronic media for new courses of study in both the academic and corporate arenas. In this paper we consider the feasibility of teaching appropriate knowledge and skills in professional communication by using converging modalities in flexible delivery (including print materials and Web-based learning) to provide for distance education. An analysis is given of literature and the authors' own experiences of communication education in undergraduate and postgraduate courses in professional communication in Australia in the School of Communication and Media at the University of Western Sydney, Nepean, and the Faculty of Education at the University of Technology, Sydney. Four case studies are used to explore seven main themes for facilitating flexible modes of distance education: learning style; personal contact with academic staff; interactivity and learning communities; technical and other support; computer mediated communication and learning; student problems with technology; and implications for academic staff.